A experiência da formação da identidade da consciência: uma análise da certeza sensível à dialética do senhor e do escravo na Fenomenologia do Espírito de Hegel - Maria Cristina Barth (2004)
Through the trajectory that conscience broaders from its's first figureSensitive Certainty - to the figure of the Dialectic of the Lord and the Slave, in the workmanship Phenomenology of Spirit, this work's aim is to do an analysis throughout the dynamic construction of the identity during this process of formation, in such a way, it studies the elements that compose this way and how the relation between the identity of the conscience and the difference actually accurs.